(untitled) (Jurnal Bahasa, 2002)
This article describes the extent of modernisation and globalisation on the usage of the terms of address in the Malay family. It is found that the decrease in the usage of the terms of address are characterized by sex, groups, location, family origin, formal educational training, parent’s occupation, family status, and the number of children in the family, based on research on 1500 respondents in a local university. It is also found that the usage of the terms of address in the Malay family is becoming less effective and increasingly faded away in the present environment.